2020
DOI: 10.1093/cid/ciaa441
|View full text |Cite
|
Sign up to set email alerts
|

Are Fluoroquinolones or Macrolides Better for Treating Legionella Pneumonia? A Systematic Review and Meta-analysis

Abstract: Background The Infectious Diseases Society of America recommends either a fluoroquinolone or a macrolide as a first-line antibiotic treatment for Legionella pneumonia, but it is unclear which antibiotic leads to optimal clinical outcomes. We compared the effectiveness of fluoroquinolone versus macrolide monotherapy in Legionella pneumonia using a systematic review and meta-analysis. Methods We conducted a systematic search of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…Third, it is unclear how many of the sampled individuals had previously received or had not received a large-spectrum antibiotic therapy able to specifically target Legionella [ 83 ]. As macrolides have been extensively delivered to SARS-CoV-2 patients during the early stages of the pandemic [ 22 , 48 , 84 , 85 , 86 ], we cannot rule out that a significant share of actual co-infections with signs and symptoms of atypical pneumonia may have benefited from early antimicrobial courses [ 22 , 85 , 87 ], with their eventual impact on Legionella infections.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it is unclear how many of the sampled individuals had previously received or had not received a large-spectrum antibiotic therapy able to specifically target Legionella [ 83 ]. As macrolides have been extensively delivered to SARS-CoV-2 patients during the early stages of the pandemic [ 22 , 48 , 84 , 85 , 86 ], we cannot rule out that a significant share of actual co-infections with signs and symptoms of atypical pneumonia may have benefited from early antimicrobial courses [ 22 , 85 , 87 ], with their eventual impact on Legionella infections.…”
Section: Discussionmentioning
confidence: 99%
“…These findings lead to some important considerations: first, it is mandatory to perform urinary antigen test for Legionella at the time of hospital admission in all cases of severe CAP; this is a recommendation already contained in the current guidelines for CAP [ 12 ]. Second, if the test is not available at the time of CAP diagnosis, initial antimicrobial therapy should include a drug with in vitro activity against Legionella (azithromycin, clarithromycin, or levofloxacin); to this end, a recent systematic review found no difference in the effectiveness of fluoroquinolones vs. macrolides in reducing mortality among patients with LP [ 13 ], although very few data compared the two classes of antibiotics in some settings such as immunosuppressed patients, severe patients needing ICU admission and patients with nosocomial legionellosis [ 14 ]. Finally, a positive or negative urinary antigen test prompts withdrawal or continuation of antibiotic treatment directed at Legionella pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a recent systematic review and meta-analysis compared the effectiveness of fluoroquinolone versus macrolide monotherapy in Legionella pneumonia [ 81 ]. A total of 3525 patients from 21 publications were included in this meta-analysis.…”
Section: Antimicrobial Treatmentmentioning
confidence: 99%
“…The results of these systematic reviews and meta-analyses support the present guidelines regarding the use of a fluoroquinolone or a macrolide for the treatment of Legionella pneumonia. However, certain limitations of the current data should be recognized [ 81 83 ]. First, the usefulness of these antibiotics has not been extensively evaluated in some subgroups of patients, such as immunocompromised patients or those requiring admission to the ICU.…”
Section: Antimicrobial Treatmentmentioning
confidence: 99%